1989
DOI: 10.1177/039139888901201106
|View full text |Cite
|
Sign up to set email alerts
|

Transmembranous Transport and Adsorption of Beta-2-microglobulin during Hemodialysis using Polysulfone, polyacrylonitrile, polymethylmethacrylate and Cuprammonium Rayon Membranes

Abstract: Beta-2-microglobulin (b2M) was identified as a causative agent of amyloidosis associated with long-term hemodialysis (HD). Therefore, we examined handling of b2M during a 4-hour hemodialysis session. We compared b2M adsoprtion and diffusive/convective elimination between high-flux membranes such as polysulfone (PS; F 60®, Fresenius), polyacrylonitrile (AN 69; FiltralR, Hospal) and polyacrylonitrile (PAN, PAN 12CX2R, Asahi) and less permeable membranes such as cuprammonium rayon (CR; AM 160 HR, Asahi) and polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…While b 2 m clearance was 21.7% higher, b 2 m mass transfer into dialysate was 53% higher in mid-dilution HDF. Certainly, this finding has to be regarded with some caution because b 2 m adsorption, which can be considerably high with synthetic dialysis membranes [19], was not taken into account. To assess adsorption, spent dialysate samples (taken at the instantaneous clearance measurement time point) were analyzed for b 2 m for computing mass balance error.…”
Section: Discussionmentioning
confidence: 99%
“…While b 2 m clearance was 21.7% higher, b 2 m mass transfer into dialysate was 53% higher in mid-dilution HDF. Certainly, this finding has to be regarded with some caution because b 2 m adsorption, which can be considerably high with synthetic dialysis membranes [19], was not taken into account. To assess adsorption, spent dialysate samples (taken at the instantaneous clearance measurement time point) were analyzed for b 2 m for computing mass balance error.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the adsorption of P2M onto synthetic dialyzer membranes . The polyacrylonitrile (PAN-AN69) (AN69) membrane is one of those with a marked adsorption capacity for P2M (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Unfortunately, none of these adsorption studies has provided data about the influence of blood flow on the amount of P2M being adsorbed onto membranes.…”
Section: Methodsmentioning
confidence: 99%
“…Based on numerous studies (11,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), several general conclusions relating to the dialytic removal of ␤2M can be provided. First, negligible ␤2M removal by lowflux unsubstituted cellulosic membranes generally occurs, although certain exceptions do exist (31).…”
Section: Low-molecular Weight Protein Removal By High-flux Dialyzersmentioning
confidence: 99%